The Effect of External Auditor, Financial Distress, and Audit Committee on Audit Report Lag - Mahendra, Fachreza Desca; Rachman, Helmy (Journal of Economics, Business, and Government Challenges, 2023)
This study aims to analyze the effect of audit tenure, auditor industry specialization, financial distress utilizing the proxy of the Altman Z-Score formula, and audit committee measured by audit committee competence on audit report lag. The population includes property and real estate companies listed on the Indonesia Stock Exchange in 2020 – 2022, from which the samples of 128 data free from outlier are selected through purposive sampling. The secondary data involved in this study are derived from the companies’ financial reports and annual reports accessed from the official websites of the Indonesia Stock Exchange and respective companies, and are analyzed by multiple linear regression processed by SPSS 25 software. The research results exhibit that audit tenure and audit committee competence have no effect on audit report lag; financial distress with the proxy of Altman Z-Score formula has a positive effect on audit report lag; and auditor industry specialization has a negative effect on audit report lag.